The impact of female BMI on sperm DNA damage repair ability of oocytes and early embryonic development potential in intracytoplasmic sperm injection cycles - Jiang, Yuqing; Shen, Zhaoyang; Xu, Jianmin; Zhu, Jing; Wang, Huan; Chen, Wenhui; Sun, Yingpu; Yang, Qingling (Frontiers in Endocrinology, 2023)
Background: Obesity adversely influences the quality of oocytes and embryos and can affect DNA repair in embryos, leading to reproductive issues. However, the effects of body mass index (BMI) on DNA repair ability in oocytes during intracytoplasmic sperm injection (ICSI) cycles have not yet been investigated. Therefore, this retrospective study aimed to analyze the influence of sperm DNA damage on embryo development and reproductive outcomes in overweight/obese and normal-weight women in ICSI cycles. Methods: A total of 1,141 patients who received the first fresh ICSI cycle treatments were recruited from July 2017 to July 2021. Based on the BMI of the women, all patients were divided into normal weight (18.5≤BMI<25 kg/m2; n=824; 72.22%) and overweight/obese (BMI≥25 kg/m2; n=317; 27.78%) groups. Furthermore, according to the sperm DNA fragmentation index (DFI), these two groups were subdivided into two subgroups: DFI<30% and DFI≥30%. Results: In the normal-weight women group, the embryonic development and reproductive outcomes of ICSI cycles were not statistically different between the two subgroups (DFI<30% and DFI≥30%). However, in the overweight/obese women group, couples with a sperm DFI≥30% had a significantly lower fertilization rate (76% vs. 72.7%; p=0.027), cleavage rate (98.7% vs. 97.2%; p=0.006), and high-quality embryo rate (67.8% vs. 62.6%; p=0.006) than couples with a sperm DFI<30%. Conclusion: When injected sperm with high DFI into the oocytes of overweight/obese women, resulting in lower fertilization, cleavage, and high-quality embryo rates in ICSI cycles, and the decreased early developmental potential of embryos from overweight/obese patients may be caused by the diminished capacity of oocytes to repair sperm DNA damage.